Selecting Collard Varieties Based on Yield, Plant Habit and Bolting - Stephen M. Olson; Joshua H. Freeman (EDIS)
HS-1101, a 5-page illustrated fact sheet by S. M. Olson and J. H. Freeman, provides growers with information about collard, results of variety testing in Quincy, FL, and descriptions of varieties. Includes tables with yield and plant weight under good to optimum conditions, and yield and plant weight when grown under conditions conducive to bolting. Published by the UF Department of Horticultural Sciences, February 2007.